The origin of sub-bands in the Raman D-band of graphene - Luo, Zhiqiang (2013)
In Raman spectroscopy investigations of defective suspended graphene, splitting in the D band is observed. Four double resonance Raman scattering processes: the outer and inner scattering processes, as well as the scattering processes with electrons first scattered by phonons (“phonon-first”) or by defects (“defect-first”), are found to be responsible for these features of the D band. The D sub-bands associated with the outer and inner processes merge with increasing defect concentration. However a Stokes/anti-Stokes Raman study indicates that the splitting of the D band due to the separate “phonon-first” and “defect-first” processes is valid for suspended graphene. For graphene samples on a SiO2/Si substrate, the sub-bands of D band merge due to the increased Raman broadening parameter resulting from the substrate doping. Moreover, the merging of the sub-bands shows excitation energy dependence, which can be understood by considering the energy dependent lifetime and/or scattering rate of photo-excited carriers in the Raman scattering process.